Youthful Students’ Perception of The Nursing Profession: A Preliminary Single-group Research - Keshavamurthy CD; Theja BC (International Journal of Community Health Nursing And Practices, 2023)
Aim: This study had four objectives: (1) examine how adolescents perceive nursing before and after organized teaching programs; (2) examine how adolescents perceive nursing after structured teaching programs; (3) compare pre-test and post-test results to assess the efficacy of a structured teaching program; (4) relate the mean improvement in nursing image to particular demographic factors. Background: This study assists in identifying potential areas for improvement or any potential interventions to enhance the perception of nursing among adolescent pupils who are potential nursing students. The appearance of nurses is also significantly influencing how people perceive them. Nursing leaders will find it difficult to decide if universal standards for nursing professionals should be established given the profession's dual reputation. The nursing profession's values and dignity should be improved right now. Most young people choose their careers based on their interests, their happiness, or their desire to serve others, not on the volume of revenue they will make. Design: The term "research design" refers to a researcher's entire strategy for discovering the answers to their research questions and putting their research hypotheses to the test. The research design outlines the methods the researcher will use to produce reliable, unbiased, and understandable data. The pre-experimental design, which consists of a single group pretest and posttest with manipulation, is used to gauge how adolescents' students perceive nursing. Method: The research approach adopted for the study is an evaluative approach. The current study utilized a pre-experimental research design known as a single-group pre-test and post-test design. The sample consists of 80 students of II PUC science group who were selected for the study and put into study group. Result: The study's findings reveal that the II PUC science group students had a negative pre-test level of perception of nursing, with a total percentage of 36.7%, a mean of 56.5, and a standard deviation of 12.2 indicating a negative perception. Students in the study group made up a total of 69.4% of the post-test level of nursing's II PUC science group, with a mean of 107.7 and SD of 7.03. 32.8% of students found the structured teaching program proved effective. Conclusion: The study's findings confirm the necessity of implementing educational initiatives to foster among teenage pupils a positive perception of the nursing profession. The results of the study suggest that adolescents have a negative perception of the nursing profession. As a result, there is a need to introduce educational programs in the future that can improve their perception of the nursing profession.
Keywords: Adolescent students; Structured teaching programme; demographic factors; image; nursing